Children and adolescents with type 1 diabetes in Australasia: An online survey of model of care, workforce and outcomes. (27th July 2018) - de Bock, Martin; Jones, Timothy W; Fairchild, Jan; Mouat, Fran; Jefferies, Craig
Abstract : Aim: To survey the model of care and workforce that manages children and adolescents with type 1 diabetes (T1D) in Australasia along with glycaemic outcomes. Methods: Tertiary and regional paediatric clinics in Australia and New Zealand (NZ) caring for children and adolescents with diabetes were invited to complete an online survey assessing health‐care professional (HCP) workforce numbers and available clinical data for the 2016 calendar year. Results: A total of 38 sites responded – 25 Australian (10 tertiary, 15 regional), 13 NZ (4 tertiary, 8 regional) – representing 9715 children with T1D. HCP resourcing varied across sites, with overall HCP/100 patient ratios of: doctors: 0.36 (0.08–1.07), nurses: 0.72 (0–1.8), dieticians: 0.19 (0–0.49) and psychologist/social workers: 0.13 (0–0.36). Overall, 39% of patients used insulin pump therapy (CSII) (29.5% NZ, 40.8% Australia). Databases were being used locally by 26 sites. Thirty‐two sites reported the mean clinic HbA1c, mean HbA1c 66 mmol/mol (8.2%) (NZ = 69 mmol/mol (8.5%), Australia = 66 mmol/mol (8.2%)), with 29% of patients attaining the recommended HbA1c target of <58 mmol/mol (7.5%) (NZ = 28%, Australia = 29%). Conclusions: This is the largest Australasian paediatric T1D workforce survey to date. HCP to patient ratios remain well below international recommendations and have not changed over the last 5–7 years. Glycaemic outcomes in this population were below recommended levels in the majority of patients. There is an urgent need to reform models of care and workforce and to institute systematic benchmarking in both countries in order to prevent acute and chronic complications of T1D.